A new conformation in sarcoplasmic reticulum calcium pump and plasma membrane Ca2+ pumps revealed by a photoactivatable phospholipidic probe - Mangialavori, Irene Cecilia (2008)
The purpose of this work was to obtain structural information about conformational changes in the membrane region of the sarcoplasmic reticulum (SERCA) and plasma membrane (PMCA) Ca(2+) pumps. We have assessed changes in the overall exposure of these proteins to surrounding lipids by quantifying the extent of protein labeling by a photoactivatable phosphatidylcholine analog 1-palmitoyl-2-[9-[2'-[(125)I]iodo-4'-(trifluoromethyldiazirinyl)-benzyloxycarbonyl]-nonaoyl]-sn-glycero-3-phosphocholine ([(125)I]TID-PC/16) under different conditions. We determined the following. 1) Incorporation of [(125)I]TID-PC/16 to SERCA decreases 25% when labeling is performed in the presence of Ca(2+). This decrease in labeling matches qualitatively the decrease in transmembrane surface exposed to the solvent calculated from crystallographic data for SERCA structures. 2) Labeling of PMCA incubated with Ca(2+) and calmodulin decreases by approximately the same amount. However, incubation with Ca(2+) alone increases labeling by more than 50%. Addition of C28, a peptide that prevents activation of PMCA by calmodulin, yields similar results. C28 has also been shown to inhibit ATPase SERCA activity. Interestingly, incubation of SERCA with C28 also increases [(125)I]TID-PC/16 incorporation to the protein. These results suggest that in both proteins there are two different E(1) conformations as follows: one that is auto-inhibited and is in contact with a higher amount of lipids (Ca(2+) + C28 for SERCA and Ca(2+) alone for PMCA), and one in which the enzyme is fully active (Ca(2+) for SERCA and Ca(2+)-calmodulin for PMCA) and that exhibits a more compact transmembrane arrangement. These results are the first evidence that there is an autoinhibited conformation in these P-type ATPases, which involves both the cytoplasmic regions and the transmembrane segments